"If I Didn't Have Them, I'm Not Sure How I Would Have Coped with Everything Myself": Empowering and Supporting Parents/Carers of High-Risk Young People Assisted by Community Forensic CAMHS. Issue 1 (2nd January 2023) - Jacob, Jenna; Lane, Rebecca; D'Souza, Sophie; Cracknell, Liz; White, Oliver; Edbrooke-Childs, Julian
Abstract: Parent/carer involvement in their child's support for mental health difficulties is a critical component of effective care. 13 Community Forensic Child and Adolescent Mental Health Services (F:CAMHS) across England were developed to provide specialist support to young people at high risk of harm to self and in particular others, and their families. The aim of this study is to explore parent/carer experiences of Community F:CAMHS. Thematic analysis of interviews (N = 18, from 5 sites) was conducted. Superordinate themes generated focused on 1) facilitators; and 2) barriers to support. Subthemes generated relate primarily to facilitators, particularly empowering parents/carers through the co-production of strategies to help, "holding" cases (taking ownership), and acting on behalf of and supporting parents/carers. Managing clear, joined-up communication across multi-agencies is also of key importance. Barriers to effective support are a lack of joined-up communication at the beginning of the implementation of the services, awareness of Community F:CAMHS, and limited contact. Implications, including the need to further embed the Community F:CAMHS offering in the overall provision of support for this population are discussed. Areas for future research are identified, including the exploration of how young people's characteristics and outcomes may impact parents/carers' experiences of interacting with services.